Planning Of Walking Tour Packages Bali Harmony Green Tour In Kuta Area At PT. Sebumi Berbagi - Yohanda, Rafaela; Rusadi, Ni Wayan Purnami; Selamet, I Wayan Agus; Paristha, Ni Putu Tiya (Politeknik Internasional Bali, 2025)
Bali tourism has become a popular destination in Indonesia, attracting both international and domestic tourists. Therefore, the planning of tour packages is a crucial part of this industry, as it is related to the quality and its impact on tourist satisfaction. The purpose of this research is to understand the planning of the Bali Harmony Green Tour walking tour package in the Kuta area by PT. Sebumi Berbagi. This research uses observation, documentation, literature review, and interviews as methods, followed by data analysis. The findings of this research include the identification of both man-made and natural tourism potentials in the Kuta area, Bali, and the planning product of the Bali Harmony Green Tour walking tour package by PT. Sebumi Berbagi. Additionally, the benefits of the Bali Harmony Green Tour Walking Tour are as follows: health impacts such as cardiovascular training and improved sleep patterns from walking, economic impacts including support for local small and medium enterprises (UMKM) through participant spending, social impacts from interactions between participants and local communities, and environmental impacts by reducing pollution from fuel-powered vehicles.